MERS-CoV and SARS-CoV-1 proteins inhibit the IFN-α JAK/STAT pathway of epithelial cells, via IFN-λ-induced USP18 - Zhang, Yamei; Stevenson, Nigel J. (Frontiers in Immunology, 2026)
The recent emergence of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-2 highlights the need for greater understanding of the immune evasion mechanisms used by Coronavirus (CoVs) to subvert antiviral responses. Previous global outbreaks caused by Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV-1 were associated with high mortality rates and limited therapeutic options. Interferon (IFN)-α is the body’s natural antiviral agent; but its Janus kinase/signal transducer and activators of transcription (JAK/STAT) signalling pathway is often antagonized by viruses, thereby preventing the upregulation of essential, anti-viral IFN Stimulated Genes (ISGs). Notably, therapeutic IFN-α has disappointingly weak clinical responses in MERS-CoV and SARS-CoV-1 infected patients, indicating that these CoVs inhibit the IFN-α JAK/STAT pathway. We previously identified that MERS-CoV-non-structural protein(nsp)2 and nsp5 and SARS-CoV-1-nsp14 block the IFN-α JAK/STAT signalling pathway in human epithelial A549 cells; however, the mechanisms behind this inhibition remain unknown. In this study, we explored the factors influencing basal STAT1 and STAT2 phosphorylation and discovered that the expression of MERS-CoV-nsp2 and SARS-CoV-1-nsp14, but not MERS-CoV-nsp5, upregulated IFN-λ1/3 in A549 cells. Neutralization of IFN-λ1/3 revealed that this induction was responsible for the observed basal STAT1 and STAT2 phosphorylation, resulting in reduced responsiveness to exogenous IFN-α. Furthermore, both MERS-CoV-nsp2 and SARS-CoV-1-nsp14 induced the expression of USP18, a negative regulator of the IFN-α JAK/STAT pathway, resulting in reduced responsiveness to exogenous IFN-α. Silencing USP18 reinstated IFN-α-mediated STAT1 phosphorylation and ISG induction. Collectively, these findings shed light on the diverse strategies employed by these CoVs to evade type I IFN antiviral responses. While providing evidence for the ineffectiveness of exogenous IFN-α treatment during CoV infection, our discoveries also identify these viral proteins as potential targets for therapeutic intervention.